A study on relative humidity sensors using PVA and PMMA coating - Zuraidah*, Harith; Huda Adnan, Abdullah Zain; Malathy, Batumalay; Sulaiman Wadi, Harun (IOP Publishing Ltd, 2019)
Simple relative humidity sensors are demonstrated using tapered silica microfibers. The silica microfibers are tapered using flame brushing method to reduce the fiber's waist diameter from 128 micrometers to 2.6 micrometers. The tapered silica microfibers were then coated using polyvinyl acetate (PVA) and polymethyl methacrylate (PMMA) before it was used to sense the relative humidity. The tapered silica microfiber coated with PVA performed better compared to tapered silica microfiber coated using PMMA. The tapered silica microfiber with PVA based sensor has better sensitivity of 0.3023 dB/RH%.